ISU-ISU KONTESKTUAL DALAM PENDIDIKAN ISLAM: GLOBALISASI DAN TANTANGAN PENDIDIKAN ISLAM - A.Nasaruddin; Nursyirwan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Globalization has become one of the most influential forces shaping educational systems worldwide, including Islamic education. The rapid advancement of information technology, digital communication, and socio-cultural transformation presents both opportunities and complex challenges for Islamic educational institutions. This study aims to analyze the contextual issues of Islamic education in the era of globalization by examining its impacts on educational philosophy, curriculum development, learning innovation, teacher professionalism, and the preservation of Islamic values. This research employs a qualitative approach through library research by reviewing scholarly books, peer-reviewed journal articles, and relevant academic documents related to globalization and Islamic education. The findings indicate that globalization encourages Islamic education to become more adaptive, innovative, and competitive while maintaining its theological and ethical foundations. However, Islamic education also encounters significant challenges, including moral degradation, secularization, cultural homogenization, digital disruption, educational inequality, and the growing demand for twenty-first-century competencies.